EKSPLORASI FAKTOR-FAKTOR YANG MENGHAMBAT SISWA KELAS IX DALAM MEMAHAMI ALJABAR - Rustam Effendy Simamora; Helmi Khairullah; Suryanti Suryanti (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2022)
Algebra is a fundamental concept in the study of mathematics. However, many junior high school students, such as grade 9 students, the unit of analysis in this study, have difficulty with this topic. Exploration of the issues will be beneficial in understanding the problem and improving the effectiveness and efficiency of remedial learning or intervention for learning improvement. This qualitative study took case studies approach to investigate barriers to learning algebra. We collected data by observation, interviews, and documentation and then analyzed it using the Creswell and Creswell (2018) qualitative data analysis model. The findings revealed that the students’ barriers in learning algebra were due to these factors: interest in mathematics, self-efficacy, fundamental skills and knowledge, social skills, and teaching-learning development was lack.Keywords: algebra, barriers to learning mathematics, case study, mathematical thinking, school mathematics